2009
DOI: 10.1080/09638280802306638
|View full text |Cite
|
Sign up to set email alerts
|

Community integration: conceptualisation and measurement

Abstract: A variety of measures have been developed and validated in disability and rehabilitation research addressing different models of community integration, with additional measures originally developed in the adjacent disciplines presenting potential for application to research in community integration for individuals with disabilities. Research is needed to further clarify the multidimensional nature of community integration and to develop sound measures of community integration. To the extent that community inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…In a study of Veterans with mental illness, those who received vouchers for housing plus case management had better housing outcomes than those with just case management or outreach work, and the voucher program was more cost effective (Rosenheck, Kasprow, Frisman, & Liu-Mares, 2003). Furthermore, Tsemberis (2010) pointed out that Housing First is not only an effective strategy, but also one that promotes principles consistent with the recovery and community integration movement (Yasui & Berven, 2009). To begin, Housing First allows individuals to make choices about their housing and takes a recovery approach, with decision making shared between providers and individuals participating in Housing First.…”
Section: Rationale For Focus On Public and Community Perspectivementioning
confidence: 95%
See 1 more Smart Citation
“…In a study of Veterans with mental illness, those who received vouchers for housing plus case management had better housing outcomes than those with just case management or outreach work, and the voucher program was more cost effective (Rosenheck, Kasprow, Frisman, & Liu-Mares, 2003). Furthermore, Tsemberis (2010) pointed out that Housing First is not only an effective strategy, but also one that promotes principles consistent with the recovery and community integration movement (Yasui & Berven, 2009). To begin, Housing First allows individuals to make choices about their housing and takes a recovery approach, with decision making shared between providers and individuals participating in Housing First.…”
Section: Rationale For Focus On Public and Community Perspectivementioning
confidence: 95%
“…Understanding attitudes of community members provides valuable insight for how to assist individuals to prepare for community responses, and how to prepare communities for integration (such as by providing education to decrease stigma). Yasui and Berven (2009) describe community integration in the following manner:…”
Section: Rationale For Focus On Public and Community Perspectivementioning
confidence: 99%
“…Numerous instruments have been developed to measure participation, many of which are based conceptually on the IcF (4)(5)(6)(7)(8). However, despite apparently clear and comprehensive lists of categories, the ICF's definition of participation as "involvement in a life situation" neither specifies how participation relates to other concepts, such as social integration, nor does it clarify what participation restrictions actually mean to persons with disabilities (9).…”
mentioning
confidence: 99%
“…9,10 The CIQ has generally demonstrated good measurement properties in TBI samples (see Methods section below). In the largest principal components analysis to date, Sander et al 11 found a 3-factor solution corresponding to home, social, and productive activities to be optimal.…”
mentioning
confidence: 99%
“…10 Therefore, the current study examined the psychometric properties of the CIQ in a large sample of adults with a variety of physical disabilities. We combined multiple disability groups and analyzed them collectively for the primary analyses, because we did not have sufficient sample sizes to comprehensively examine the psychometrics of the CIQ in each of the separate disabilities.…”
mentioning
confidence: 99%